Shear-wave velocity profiling of Jizan city, southwestern Saudi Arabia, using controlled-source spectral analysis of surface-wave measurements - Alzahrani, Hassan; Abdelrahman, Kamal; Qaysi, Saleh; Al-Otaibi, Naif (Journal of King Saud University. Science, 2021)
Shear-wave velocity profiles are the main site-specific data for site classification, which are commonly used for the purposes of seismic microzonation and hazard assessment. The controlled-source spectral analysis of surface wave (CSSASW) dispersion measurements have been successfully performed to characterize seismic sites up to 30-m depths. This study utilizes the CSSASW application in Jizan City to obtain shear-wave velocity profiling at 14 sites distributed throughout the city using an electromagnetic vibrator. The recorded Rayleigh wave phase velocity dispersion curves are transformed to calculate the apparent velocity distribution in depth. Shear-wave velocities, calculated using theoretical relationships, can then be utilized to obtain design parameters for the soil strata. Shear-wave velocity varies from 216.97 to 829.59 m/s through Jizan City indicating the remarkable change of the near-surface sediments. The hard soil profiles of soft rock that were revealed by Vs values in this terrain (sites No. 7, 8, and 13) can be attributed to the existence of a dense layer of salt rock. Construction in such areas is prohibited due to the high susceptibility of large settlements in foundations as a consequence of salt dissolution. In the Sabkha terrains, all soil profiles were related to Vs, defined as stiff soils that were then modified to a softer class owing to their high liquefaction potential. These results should be considered before establishing important and strategic projects in the city.